Hybrid Surgery Options for Complex Clinical Scenarios in Adult Patients with Congenital Heart Disease: Three Case Reports - Rapetto, Filippo; Kenny, Damien; Turner, Mark; Parry, Andrew; Stoica, Serban; Uzun, Orhan; Caputo, Massimo (Frontiers in Surgery, 2017)
Hybrid procedures performed by cardiac surgeons and interventional cardiologists are becoming increasingly preferred for the treatment of adult patients with complex congenital heart disease (CHD). We report 3 cases of adult patients previously operated for CHD and recently treated with a hybrid approach in our institution. Case 1: A 76 year old woman with permanent atrial fibrillation, lung disease, chronic kidney disease, microcytic anemia and type II diabetes mellitus, previously operated for ASD closure and pulmonary valvotomy, presented with severe pulmonary regurgitation and advanced right ventricular failure. In order to minimize the surgical risk, a hybrid approach was used: an extensive right ventricular outflow tract (RVOT) plication was followed by implantation of an Edwards Sapien XT prosthesis in the RVOT through the right ventricular apex, without cardiopulmonary bypass. Case 2: A 64 year old man with previous atrial septum excision and pericardial baffle for partial anomalous pulmonary venous drainage with intact interatrial septum, presented with worsening dyspnoea, right ventricular failure and pulmonary hypertension caused by baffle stenosis. His comorbidities included coronary artery disease, atrial flutter and previous left pneumonectomy. After performing a redo longitudinal median sternotomy, a 20 mm stent was implanted in the baffle with access through the superior vena cava. Case 3: A 50 year old man, with previous atrioventricular septal defect repair, followed by mitral valve replacement with a mechanical prosthesis, subsequently developed a paravalvular leak with severe mitral regurgitation and severe left ventricular dysfunction. He underwent a transapical paravalvular leak device closure with two Amplatzer Vascular Plugs. The treatment strategy choice for the management of adult patients with CHD often represents a challenge for cardiac surgeons and cardiologists due to complex anatomy, wide range of clinical presentations and a high risk profile. In our opinion, hybrid surgery is a safe and promising therapeutic modality that increases the available treatment options for this patient population. A multidisciplinary and patient-tailored approach is crucial in these complex clinical scenarios.